Analysis of Potential and Development Strategies for Sama Guna Village as a Sport Tourism Village - Maulana, M. Reza Agista; Adhitya, Bagus Singandaru; Hulfa, Ihyana (Laboratorium Riset Ekonomi, 2024)
This research explores the potential and strategies for developing Sama Guna Village in North Lombok Regency as a sport tourism destination. Sama Guna Village offers rich natural beauty, cultural heritage, and diverse plantation commodities, positioning it as an ideal location for activities such as rafting, hiking, and cultural tourism. Despite its potential, the village faces challenges such as inadequate infrastructure, limited promotional efforts, and a lack of essential facilities. Using a qualitative research approach, the study identifies key strategies, including infrastructure improvement, development of unique tourism products, enhancement of human resources, and collaboration with stakeholders. The proposed initiatives aim to establish Sama Guna Village as a sustainable sport tourism hub, offering both economic benefits to the community and unique experiences for visitors. Emphasizing sustainable tourism principles, this research serves as a reference for policymakers and tourism managers to address current shortcomings and implement effective development strategies. Collaborative efforts between local communities, private sectors, and the government are essential to transform Sama Guna Village into a prominent sport tourism destination in Indonesia. Keywords: Sport tourism; rural tourism development; Sama Guna Village; sustainable tourism; North Lombok Regency